Hubungan Pengetahuan Ibu Hamil dengan Perilaku Pencegahan Stunting di Bidan Praktik Mandiri - Yuniyanti pakage Pakage; Wira Daramatasia; Angernani Trias Wulandari (Media Husada Journal Of Nursing Science, 2026)
Background: Stunting is a chronic nutritional problem that has an impact on growth, cognitive development, and the quality of human resources in the future. Stunting prevention needs to start from pregnancy, one of which is through increasing pregnant women's knowledge about nutrition and health. Knowledge plays an important role in influencing behavior because it functions as a predictor or foundation in behavior. Objective: To analyze the correlation between maternal knowledge and stunting prevention behavior during pregnancy. Methods: The design in this study used correlational analytics with a cross-sectional approach. The population in this study is pregnant women in the Independent Practice Midwife of Tunggulwulung Village, Mojolangu Community Health Center Working Area as many as 32 people, and a sample of 28 people taken by purposive sampling. Data analysis using Somers'D.Results: The results indicated that most of the good knowledge, 17 people (53.6%), most of the stunting prevention behaviors were sufficient, namely 11 people (64.3%), and there was a correlation between knowledge and stunting prevention behavior, p-value = 0.006 and moderate strength (r = 0.418).   Keywords: Pengetahuan, perilaku pencegahan stunting, Ibu hamil